The mirror roots of social cognition - Sinigaglia, Corrado; Sparaci, Laura (Acta Philosophica, 2008)
This paper illustrates how social interchange characterized by forms pragmatic understanding and emotional coloring are grounded on mirror mechanisms. Initial paragraphs will outline the anatomical architecture of the mirror neuron system for action in monkeys and humans and their main functions. Paragraph four will introduce the theme of emotional understanding underscoring its relevance in development and illustrating major studies on mirror neurons and emotions, before proceeding to consider specific cases in how social cognition is impaired as in autistic spectrum disorders.